Tradisi Ma' Ballak Bua Bagi Orang Sakit dan Relevansinya dengan Pengakuan Dosa dalam Iman Kristen - Silta Omega Monni'; Restifani Cahyami (CARAKA: Jurnal Teologi Biblika dan Praktika, 2022)
This paper is based on the background of the problem that the author sees about a tradition of “Ma’ Ballak Bua” confession in Bonggakaradeng, Tana Toraja which accepted and is still practiced by Christians in the area and is considered to have something to do with confession in the Christian faith. This research was conducted to achieve a goal, namely to explain the tradition of Ma’ Ballak Bua for the sick and its relationship with confession of sins in the Christian faith. The research method used is a qualitative research method with an ethnographic approach through library research and interviews. The results showed that Ma’ Ballak Bua and confession have the same goal, namely to express guild and ask God for forgiveness for all sins committed during life in order to bring peace or forgiveness in life.